Assessing nursing skills in the clinical environment. Issue 5 (3rd May 2016) - Williams, Sarah
Abstract: Assessment is essential to encourage learning and ensure that students are achieving a minimum standard (May & Head, 2010 ). There are two types of assessment, formative and summative; both will be discussed with regard to assessing practical skills. Objective Structured Clinical Examinations (OSCEs) will be the main focus of the article. The pros and cons of this style of assessment will be discussed in addition to providing a brief overview of other assessment options.